Analysis of PSAK 69 Implementation on Biological Assets to Support Financial Statement Relevance at PT. Berdikari United Livestock (PT. BULS) Sidenreng Rappang - Hasdiana; Hernianti Harun; Aida Gimawati; Mawaddah Rachman (IECON: International Economics and Business Conference, 2025)
This study aims to analyze the implementation of PSAK No. 69: Agriculture regarding Biological Assets at PT. Berdikari United Livestock (PT. BULS) Sidenreng Rappang. The research was conducted using a qualitative case study approach. Data were collected through observation, documentation, and interviews with the Secretary, Accounting and Finance Department, and Operations Department of PT. BULS. The research findings indicate that although PT. BULS recognizes a Biological Assets account in its financial statements, the company still classifies livestock — its primary operational asset — under current assets. Furthermore, the valuation is based on acquisition cost instead of fair value, which does not align with the provisions of PSAK No. 69. The company has managed to categorize livestock by type and age in accordance with the standard, but has yet to apply fair value measurement and disclosure optimally. This research contributes to the accounting literature by providing a case analysis of PSAK 69 implementation challenges in livestock companies, particularly state-owned subsidiaries. Practically, the findings offer recommendations for PT. BULS and similar entities to enhance their financial reporting quality by adopting proper biological asset accounting practices. The study highlights that the main obstacle lies in the limited understanding of PSAK 69 among accounting personnel and the difficulty in determining fair value due to market price volatility. It is recommended that companies collaborate with certified public appraisers (KJPP) and conduct regular staff training on PSAK 69 application to improve financial statement relevance and reliability